Answer: The answer is ax + by = c.
Step-by-step explanation: We are given to write the equation of a straight line in general form.
We know that a straight line is always represented by a linear equation with two unknown variables, where the coefficients are constants.
A linear equation in two variables 'x' and 'y' with constant coefficients 'a', 'b' and 'c' is
ax + by = c.
Therefore, the general form of the straight line is
ax + by = c.
For example, if a = 2, b = 3 and c = 1, then the equation of the line becomes 2x + 3y = 1. The graph of this straight line is shown in the attached figure.
Thus, the equation is ax + by = c.